Bioinstructive microparticles for self-assembly of mesenchymal stem Cell-3D tumor spheroids. (December 2018) - Ferreira, L.P.; Gaspar, V.M.; Mano, J.F.
Abstract: 3D multicellular tumor spheroids (3D-MCTS) that closely mimic in vitro the complex lung tumor microenvironment (TME) are highly desirable for screening innovative anti-cancer therapeutics. Despite significant improvements in mimicking lung TME, few models have combined tumor-infiltrating mesenchymal stem cells from bone marrow (hBM-MSCs) with heterotypic 3D tumor spheroid models containing ECM mimetic components. Herein, we engineered hybrid 3D-MCTS that combine, for the first time, A549:fibroblasts:hBM-MSCs in heterotypic tri-culture, with bioinstructive hyaluronan microparticles that act as tumor-ECM mimetics and as cell-anchoring hotspots. The obtained results indicated that 3D microspheres provided proper support for cells to self-assemble into compact 3D microtissues and promoted an increase in CD44 expression, emulating the presence of native-ECM hyaluronan. 3D-MCTS size and sphere-like morphology was reproducible and tri-culture models presented the characteristic solid tumors necrotic core. Mesenchymal stem cells tracking demonstrated that hBM-MSCs migrate to different regions in 3D microtumors mass exhibiting dynamic interactions with cancer cells and stromal fibroblasts, alike in human tumors. Importantly, doxorubicin administration revealed hBM-MSCs effect on cytotoxic responses in 3D tri-culture models and in dual cultures of hBM-MSCs:A549 at 10:1 ratio. Such findings evidence the relevance of including hBM-MSCs in combination with cancer-stromal fibroblasts in 3D in vitro tumor models and the importance to test different cell-to-cell ratios to mimic tumor heterogeneity. In addition, bioinstructive hyaluronan-microparticles were also effective as cell-agglomerating scaffolds and showed potential to be used as an enabling technology for including different ECM components in 3D in vitro models in the future.